LABOR WELFARE AFFECTS EMPLOYEE PERFORMANCE AND IS MEDIATED BY WORK SPIRIT - Sarman, Rohmat; Kartika, Ranti (Jurnal Riset Bisnis dan Manajemen, 2023)
This study aims to analyze how the influence of labor welfare on employee performance is mediated by morale at PT. Area PGE Kamojang, either directly or indirectly. The research method used was a descriptive and verification method with a total sample of 74 employees. Data collection techniques used were interviews, questionnaires, and observation. Data analysis methods used in this study include path analysis, multiple linear regression analysis, coefficient of determination, and hypothesis testing. The results of the study show that the welfare of the workforce has a direct effect on morale. Labor welfare has a direct effect on employee performance, just as work enthusiasm has a direct effect on employee performance. Then, the results of the analysis also show that morale can mediate the influence of labor welfare on employee performance.